EduSymp 2011 - Preface - Winter, Andreas; Brandsteidl, Marion (Electronic Communications of the EASST, 2012)
The Educators’ Symposium focuses on the wide topic of software modeling education ranging from experience reports and case studies to novel pedagogical approaches. Traditionally collocated with the ACM/IEEE International Conference on Model-Driven Engineering Languages and Systems (MODELS), it offers the opportunity for teachers from both academia and industry to present and discuss new ideas and challenges concerning software modeling education. This preface shortly reports on the 7th edition of the Educators’ Symposium held in October 2011 in Wellington, New Zealand.